Experimental and numerical studies of prefabricated structures using CFST frame and composite wall. (1st May 2022) - Bian, Jinliang; Cao, Wanlin; Qiao, Qiyun; Zhang, Jianwei
Abstract: A prefabricated structure composed of a lightweight concrete filled steel tube (CFST) frame and an embedded steel plate (ESP) composite wall is proposed, known as a CFST frame–ESP composite wall. To study the seismic performance of the prefabricated structure, low reversed cyclic loading tests of six full-scale specimens were performed, including five CFST frame–ESP composite walls with different wall details and one bare frame. The failure characteristics, hysteretic characteristics, bearing capacity, stiffness degradation, and energy dissipation capacity of the specimens were compared, and a simplified model was used for the ESP composite wall. Based on OpenSees finite element software, finite element simulation and parameter analysis were performed using a simplified model. The calculated results agree well with the experimental results. The results show that the ESP composite wall can improve the bearing capacity, initial stiffness, and energy dissipation capacity of the CFST frame significantly. The use of a rebar brace decreased the concrete damage and increased the ultimate bearing capacity, initial stiffness, and energy dissipation capacity of the ESP composite wall. The mechanical characteristics of the EPS composite wall is considered in the simplified model. The modeling method presented herein can be used to analyze the abovementioned type of structure. Highlights: A total of 6 full-scale specimens were tested under low reversed cyclic loading. The ESP composite wall can significantly improve the seismic performance of the CFST frame. The rebar brace decreased the concrete damage and increased the seismic performance of the ESP composite wall. A simplified model was proposed to simplify the CFST frame-ESP composite wall structure.